2020
DOI: 10.1210/clinem/dgaa619
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Restriction Therapy for Chronic SIAD; Results of a Prospective Randomized Controlled Trial

Abstract: Context Fluid restriction (FR) is the recommended first-line treatment for syndrome of inappropriate antidiuresis (SIAD), despite the lack of prospective data to support its efficacy. Design A prospective non-blinded randomised controlled trial of FR versus no treatment in chronic SIAD. Interventions and Outcome 46 patients with chronic asymptomatic SIAD were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…We, however, only managed patients with documented hyponatraemia with fluid restriction during inpatient stay; we think this approach provides more robust data about the efficacy of fluid restriction in treating SIADH as applying treatment in the outpatient setting may be liable to missing some data, particularly with respect to daily serum sodium response. Finally, the mean sodium increase of 3.3 mmol/L after 3-day fluid restriction reported in our study is almost identical to the increase documented in the first ever, and only so far, randomised controlled trial of fluid restriction [11].…”
Section: Comparison With Other Studiessupporting
confidence: 89%
“…We, however, only managed patients with documented hyponatraemia with fluid restriction during inpatient stay; we think this approach provides more robust data about the efficacy of fluid restriction in treating SIADH as applying treatment in the outpatient setting may be liable to missing some data, particularly with respect to daily serum sodium response. Finally, the mean sodium increase of 3.3 mmol/L after 3-day fluid restriction reported in our study is almost identical to the increase documented in the first ever, and only so far, randomised controlled trial of fluid restriction [11].…”
Section: Comparison With Other Studiessupporting
confidence: 89%
“…The proportion of patients achieving a pNa ⩾ 130 mmol/L was 61% and 71% after 3 and 30 days treatment respectively. 54 While the modest improvements in pNa and the favourable safety profile, justify the position of FR as first-line therapy, the data from this study challenge the effectiveness of the treatment in a significant proportion of patients. This highlights the need for effective and affordable second-line treatments for chronic SIAD.…”
Section: Impact Of Treatment Of Hyponatraemia; Why Should We Treat It?mentioning
confidence: 83%
“…Thus, the European guidelines recommended the use of urine osmolality and urine sodium concentrations as key steps in the assessment of the etiology of hyponatremia ( 9 ). Another reason contributing to the diagnostic dilemma is that SIADH is a diagnosis of exclusion ( 4 , 9 , 22 ) and the first-line therapy of SIADH (fluid restriction) does not always work ( 23 ), perplexing the physician further. While urine sodium concentrations <30 mmol/L signify a low effective arterial blood volume and have a high negative predictive value for SIADH ( 5 ), it is unclear what the upper threshold is to differentiate SIADH from other causes of natriuresis (e.g., renal salt wasting or CSW).…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that high levels of urine sodium and urine osmolality were individually associated with non-response to fluid restriction [odds ratio (OR) 15.0, 95% confidence interval (CI) 2.4–95.8, P = 0.004 and OR 34.8, 95% CI 1.2–1038.8, P = 0.041, respectively] ( 12 ). A randomized controlled trial studying 46 patients with SIADH and their response to fluid restriction found that baseline urine osmolality or urine/plasma electrolyte ratio did not predict treatment response to fluid restriction, however the study was underpowered ( 23 ). In another study of 84 cases of SIADH after head injury, the severe SIADH group compared with the mild SIADH group had higher urine osmolality and 24-h urine sodium concentrations (41–250 vs. 32–106 mmol/L) ( 36 ).…”
Section: Discussionmentioning
confidence: 99%